2021
DOI: 10.3390/biology10080735
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome Prediction in COVID-19 Patients by Lymphocyte Subsets Analysis and Monocytes’ iTNF-α Expression

Abstract: In December 2019, a novel coronavirus, “SARS-CoV-2”, was recognized as the cause of coronavirus disease 2019 (COVID-19). Several studies have explored the changes and the role of inflammatory cells and cytokines in the immunopathogenesis of the disease, but until today, the results have been controversial. Based on these premises, we conducted a retrospective assessment of monocyte intracellular TNF-α expression (iTNF-α) and on the frequencies of lymphocyte sub-populations in twenty-five patients with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Symptoms related to COVID-19 can be unspecific, but often include fatigue, fever and dry cough [12]. Unusual symptoms include nasal congestion, gastrointestinal discomfort, headache, conjunctivitis, pains and aches, as well as loss of taste and smell, lymphopenia, and prolonged symptomatic experience with antimicrobial therapy (at least 3 days) [6,13]. COVID-19 has also been associated with coagulation disorders, secondary bacterial infections, immunodeficiency and myocardial as well as hepatic, and renal injury [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms related to COVID-19 can be unspecific, but often include fatigue, fever and dry cough [12]. Unusual symptoms include nasal congestion, gastrointestinal discomfort, headache, conjunctivitis, pains and aches, as well as loss of taste and smell, lymphopenia, and prolonged symptomatic experience with antimicrobial therapy (at least 3 days) [6,13]. COVID-19 has also been associated with coagulation disorders, secondary bacterial infections, immunodeficiency and myocardial as well as hepatic, and renal injury [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a trend toward functional impairments and decreased levels of circulating Tregs in severe cases of COVID-19 has been reported previously ( 38 40 ). It was shown that patients dying from COVID-19 exhibited significantly lower Treg counts and higher Th17/Treg ratio compared to recovered and healthy controls ( 42 44 ) and that low Treg counts at hospital admission were associated with clinical worsening and longer duration to discharge ( 45 , 46 ). Correspondingly, several studies demonstrated a downregulation of FoxP3 in severe cases of COVID-19 ( 44 , 47 – 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a trend toward functional impairments and decreased levels of circulating Tregs in severe cases of COVID-19 has been reported previously (3335). It was shown that patients dying from COVID-19 exhibited significantly lower Treg counts and higher Th17/Treg ratio compared to recovered and healthy controls (3739) and that low Treg counts at hospital admission were associated with clinical worsening and longer duration to discharge (40, 41). Correspondingly, several studies demonstrated a downregulation of FoxP3 in severe cases of COVID-19 (39, 42–44).…”
Section: Introductionmentioning
confidence: 99%